The Moderation Effect of Approach Motivation Between Schizotypy and Creative Ideational Behavior - Wang L; Pei Y; Zhu Y; Long H; Pang W (Psychology Research and Behavior Management, 2024)
Lixia Wang,1,* Yilai Pei,2,* Yuanfei Zhu,1 Haiying Long,3 Weiguo Pang4 1Shanghai Teacher Institute, Shanghai, People’s Republic of China; 2China Institute of Education and Social Development, Beijing Normal University, Beijing, People’s Republic of China; 3Department of Educational Psychology, University of Kansas, Lawrence, KS, USA; 4School of Psychology and Cognitive Science, East China Normal University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haiying Long; Weiguo Pang, Email hlong@ku.edu; wgpang@psy.ecnu.edu.cnIntroduction: The schizotypy-creativity link has been studied from different perspectives over the past few decades, yet the results of this relationship are inconsistent in the literature. Previous studies have suggested that two basic motivational systems—Behavioral Inhibition System (BIS, avoidance motivation) and Behavioral Activation System (BAS, approach motivation)—underlie the relationship between schizotypy and creativity. Few empirical studies, however, have examined how the relationship interacts with other variables. This study fills these gaps and explores the role of the approach and avoidance motivation assessed by trait behavioral activation and inhibition in the link between schizotypy as a dimensional personality trait and creative ideational behavior as a measure of creativity.Method: Undergraduate students (N = 388) completed questionnaires including the Schizotypal Personality Questionnaire (SPQ) measuring 3 dimensions of schizotypy, Runco Ideational Behavior Scale (RIBS) measuring creative ideational behavior, and BIS/BAS Scales measuring trait behavioral motivation. Bivariate Pearson correlation was computed, and hierarchical linear regression was performed to explore the effects of schizotypy, BIS/BAS, and their interaction on creative ideational behavior. The conditional effect of schizotypy based on different levels of the moderator was further tested.Results: The total score, positive dimension and disorganized dimension of SPQ were all positively correlated with RIBS, BAS, and BIS. Negative dimension of SPQ was not significantly correlated with the RIBS score but was positively correlated with BIS. Additionally, after controlling gender and age, BAS significantly moderated the relationship between the positive and disorganized dimensions of schizotypy and creative ideational behavior measured by RIBS. However, BIS was not a significant moderator.Discussion: The findings of this study regarding the relationships between different dimensions of schizotypy, two motivational systems, and creative ideational behavior were mostly consistent with previous findings. The significant moderated effect of BAS on the relationship between two dimensions of schizotypy and creative ideational behavior made significant contributions to the understanding of the relationship between schizotypy and creativity.Keywords: schizotypy, creativity, creative ideational behavior, motivation